Putting the Self in Self-Correction: Findings From the Loss-of-Confidence Project. (November 2021) - Rohrer, Julia M.; Tierney, Warren; Uhlmann, Eric L.; DeBruine, Lisa M.; Heyman, Tom; Jones, Benedict; Schmukle, Stefan C.; Silberzahn, Raphael; Willén, Rebecca M.; Carlsson, Rickard; Lucas, Richard E.; Strand, Julia; et al.
Science is often perceived to be a self-correcting enterprise. In principle, the assessment of scientific claims is supposed to proceed in a cumulative fashion, with the reigning theories of the day progressively approximating truth more accurately over time. In practice, however, cumulative self-correction tends to proceed less efficiently than one might naively suppose. Far from evaluating new evidence dispassionately and infallibly, individual scientists often cling stubbornly to prior findings. Here we explore the dynamics of scientific self-correction at an individual rather than collective level. In 13 written statements, researchers from diverse branches of psychology share why and how they have lost confidence in one of their own published findings. We qualitatively characterize these disclosures and explore their implications. A cross-disciplinary survey suggests that such loss-of-confidence sentiments are surprisingly common among members of the broader scientific population yet rarely become part of the public record. We argue that removing barriers to self-correction at the individual level is imperative if the scientific community as a whole is to achieve the ideal of efficient self-correction.